Monitoring Overtraining in Athletes - Hooper, S. L.; MacKinnon, L. T. (Sports Medicine, 1995)
While attempting to maximise training benefits, athletes may become overtrained, frequently exhibiting signs and symptoms of overtraining syndrome including chronic, high levels of fatigue, stagnancy or deterioration in performance and mood changes.[1-3] Although there is no indication that overtraining causes irreversible damage to the athlete, the risk of injury, illness and premature retirement is increased.[4-6] Rest or greatly reduced training over several weeks or months may be needed for complete recovery.[2,3,7] It is often difficult for the coach to intuitively provide optimal work loads for every athlete based solely on perception of the athlete's training tolerance and recovery capacity. Moreover, the highly motivated athlete may intentionally mask the early warning signs of imminent overtraining syndrome in order to continue training. These highly competitive athletes are often prepared to risk the onset of overtraining syndrome in order to achieve their goals. Identification of markers of overtraining would allow coaches and athletes to confidently adjust training loads to maximise training benefits yet avoid overtraining, thereby, optimising performance. The purpose of this leading article is to provide recommendations for the monitoring of overtraining in athletes. In the process, this review will highlight some of the problems associated with determining the appropriate method for monitoring athletes. Overtraining and overtraining syndrome have been extensively reviewed in several recent papers[1-3] and this paper does not attempt to present the current state of knowledge on this topic.